Characterization of Gut Microbiome in Liver Transplant Recipients With Nonalcoholic Steatohepatitis. Issue 12 (December 2020) - Satapathy, Sanjaya K.; Banerjee, Pratik; Pierre, Joseph F.; Higgins, Daleniece; Dutta, Soma; Heda, Rajiv; Khan, Sabrina D.; Mupparaju, Vamsee K.; Mas, Valeria; Nair, Satheesh; Eason, James D.; Kleiner, David E.; et al.
Abstract : Background: Nonalcoholic fatty liver disease (NAFLD) and its progressive form nonalcoholic steatohepatitis (NASH) are a growing problem globally and recur even after liver transplant (LT). We aim to characterize the gut dysbiosis in patients who developed recurrent NAFLD compared with patients without recurrence following LT. Methods: Twenty-one patients who received LT for NASH and had a protocol liver biopsy performed beyond 1-y post-LT were included prospectively (January 2018–December 2018). Genomic DNA extraction, next-generation sequencing, and quantitative PCR analysis were performed on stool samples collected within 1.1 ± 1.6 y from time of liver biopsy. Results: Recurrent NAFLD was noted in 15 of the 21 included patients. Stool microbiome analysis at the genus level showed significant loss of Akkermansia and increasing Fusobacterium associated with NAFLD recurrence. Quantitative PCR analysis revealed significantly decreased relative abundance of Firmicutes in patients with NAFLD activity scores (NASs) ≥5 as compared with patients with lower NAS scores, whereas Bacteroidetes were significantly increased with higher NAS ( P < 0.05). Firmicutes ( P = 0.007) and Bifidobacterium group ( P = 0.037) were inversely correlated, whereas Bacteroidetes ( P = 0.001) showed a positive correlation with higher hepatic steatosis content. The Firmicutes/Bacteroidetes ratios were higher in patients without NAFLD or NASH as compared with patients diagnosed with NAFLD or NASH at the time of sample collection. Conclusions: Akkermansia, Firmicutes, and Bifidobacterium may play protective roles in the development of recurrent NAFLD in LT recipients, whereas Fusobacteria and Bacteroidetes may play pathogenic roles. These findings highlight the potential role of the "gut-liver" axis in the pathogenesis of NAFLD recurrence after LT. Abstract : Supplemental Digital Content is available in the text.